Hate Speech Law Enforcement in Indonesia - Ryan Rainhard Marchello (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Information technology that is currently developing will make it easier for people to know or communicate remotely in various parts of the earth instantly in a matter of seconds though. The facilities used started from radio, television, telephone set, mobile phone, telegram, facsimile, and the internet. The ease of using the internet besides having a positive impact, but in the field of law, especially criminal law, also has a negative influence, namely causing a paradigm shift in the study of crime, especially hate speech crimes. The handling of hate speech crimes is based on the Criminal Code, Law No. 11 of 2008, Law No. 40 of 2008, Law No. 7 of and Regulation of the Chief of the National Police of the Republic of Indonesia No. 8 of 2013. In terms of evidence, revealing whether someone's actions can be categorized as hate speech is based on the evidence regulated in the Criminal Procedure Code. The ITE Law itself has actually formulated what can be used as evidence in examining hate speech cases on social media, but there is still confusion.